Major Vault Protein Promotes Hepatocellular Carcinoma Through Targeting Interferon Regulatory Factor 2 and Decreasing p53 Activity. Issue 2 (23rd March 2020) - Yu, Haisheng; Li, Mengqi; He, Rui; Fang, Peining; Wang, Qiming; Yi, Yu; Wang, Fubing; Zhou, Li; Zhang, Yi; Chen, Aidong; Peng, Nanfang; Liu, Dan; et al.
Abstract : Background and Aims: Major vault protein (MVP) is up‐regulated during infections with hepatitis B virus (HBV) and hepatitis C virus (HCV). Here, we found that MVP deficiency inhibited hepatocellular carcinoma (HCC) development induced by diethylnitrosamine, hepatitis B X protein, and HCV core. Approach and Results: Forced MVP expression was sufficient to induce HCC in mice. Mechanistic studies demonstrate that the ubiquitin ligase human double minute 2 (HDM2) forms mutual exclusive complexes either with interferon regulatory factor 2 (IRF2) or with p53. In the presence of MVP, HDM2 is liberated from IRF2, leading to the ubiquitination of the tumor suppressor p53. Mouse xenograft models showed that HBV and HCV promote carcinogenesis through MVP induction, resulting in a loss of p53 mediated by HDM2. Analyses of clinical samples from chronic hepatitis B, liver cirrhosis, and HCC revealed that MVP up‐regulation correlates with several hallmarks of malignancy and associates with poor overall survival. Conclusions: Taken together, through the sequestration of IRF2, MVP promotes an HDM2‐dependent loss of p53 that promotes HCC development.